Tiger Economies Under Threat : A Comparative Analysis of Malaysia's Industrial Prospects and Policy Options - Yusuf, Shahid (World Bank, 2012)
The Southeast Asian Tigers feel threatened. Even though their growth rates have remained above the average for the world and also above the average for developing countries, their economic performance falls short of that in the first half of the 1990s. The underlying worry is that it presages the beginning of a downward trend, the harbingers of which are lower rates of investment, persistently low rates of total factor productivity, and low levels of innovativeness. The Southeast Asian Tigers' worries motivate three questions, which this book attempts to answer. First, are the Tigers rightly threatened by a creeping economic sclerosis or what some observers are calling the middle-income trap? Second, if the threat is real, what are the underlying causes? Third, are there ways of neutralizing the problems and at least maintaining if not raising the growth rates of the recent past? This book will respond to these questions by means of a comparative analysis of the Tiger economies that is centered on Malaysia. This analysis draws on a comprehensive set of techniques and indicators to assess competitive pressures, to gauge industrial and technological capabilities, and to indicate some of the directions industrial change in Southeast Asia could take. Thus, the book seeks not only to view industrial evolution in the region from a comparative perspective taking account also of what is happening and has happened in other parts of East Asia but also to illuminate this ongoing and uncertain process using some of the latest empirical techniques devised for this purpose. The balance of this chapter provides the developmental and international contexts with reference to which these questions will be addressed. It explains the book's preferred angles to tackling them. The chapter also outlines the contents of the volume and foreshadows the principal findings and conclusions.